Human Resource Practice Innovation for Enhancing Workforce Agility in the Natural Resource Economy Sector during the Digital Era. - Syamsu Rijal; Muhlis (International journal of technology and education research, 2026)
The rapid acceleration of the digital economy between 2020 and 2025 has forced traditional sectors to undergo radical transformations, yet empirical evidence regarding workforce adaptation in the extractive industries remains scarce. This study investigates the impact of Human Resource (HR) practice innovation on enhancing workforce agility within Indonesia's natural resource economy sector. Using a quantitative approach with PLS-SEM analysis of simulated data from 450 professionals in the mining, energy, and plantation industries, this research evaluates how digitally based HR interventions—such as AI-driven recruitment, VR-based safety training, and real-time performance analytics—influence employee adaptability and resilience. The results reveal that HR practice innovation significantly predicts workforce agility (β = 0.542, p < 0.001), explaining 48.9% of its variance. Notably, technology-driven training emerged as the most potent catalyst for agility, particularly in mitigating operational risks in remote locations. The findings suggest that for Indonesian natural resource firms, digitalizing human capital management is not merely an administrative upgrade but a strategic imperative to achieve organizational resilience amidst global commodity volatility and the green energy transition. This study contributes to the Resource-Based View (RBV) by demonstrating that agile human capital, fostered through innovative HR practices, serves as a unique competitive advantage in the Industry 4.0 era. Practical recommendations for HR managers and policymakers focus on bridging the digital skills gap to ensure long-term sectoral sustainability.